A new model to teach literature for pre-training teaching programmes in Malaysian schools - Abdullah, Tina; Zakaria, Mohamad Hassan; Ismail, Fauziah; Wan Mansur, Wan Fara Adlina; Abd. Aziz, Marzilah (Faculty of Management and Human Resource Development, 2005)
This research was carried out to determine the current practice and perception that teachers and students have about the Literature Component incorporated into the English language subject designed for the Kurikulum Bersepadu Sekolah Menengah (KBSM). The information acquired from this research was used to propose a suitable teaching model that could be adopted in the training of pre-service teacher trainees in the Teaching English as a Second Language (TESL) programme in Universiti Teknologi Malaysia. For data collection, two sets of questionnaires were designed. The first set was distributed to 26 secondary school teachers; while the other set was circulated among 420 form one to form five secondary school students in the area of Johor Bahru. The overall findings of this research show that both teachers and students have very positive perception of the teaching and learning of the Literature component in the English language subject. However, a significant finding of this research shows that there is a difference in the methodological approaches applied in the teaching of literature by experienced English language teachers as opposed to the inexperienced ones. Based on the results of this research, a teaching model suitable to be used to teach literature in the Malaysian context was recommended to be used in the training of the future TESL teachers to become creative and confident of using literature in teaching the English language.